Exploring EFL Teachers’ Practices Flipped Classroom Through Think-Pair Share Strategy In Reading Comprehension - Fitriani, Rizka; Andrie, Chaerul; Reza Pahlevi, Muhammad (Peneliti.net, 2024)
This study investigates of EFL teacher practices using flipped classroom and Think-Pair Share (TPS) strategy in reading comprehension classes. The purpose of this study is to find the challenges and opportunities encountered by EFL teacher while utilizing this learning model. This investigation applied a qualitative methodology with a case study design. This study's participant was an EFL teacher who taught at a private junior high school in Bekasi, West Java. The researcher used observation, interviews, and documentation to collect the data. By employing thematic analysis by Braun & Clarke (2006), the data is analyzed. The research findings indicate that flipped classroom and TPS serve a meaningful learning task that facilitates text comprehension among students. In addition, the use of flipped classrooms and TPS incorporates challenges and opportunities. This study encounters practical difficulties and school policies as obstacles. In addition, there are opportunities to exercise student-centered learning, assist students with learning readiness, and improve students' reading comprehension